Methanol Fractionation of Softwood Kraft Lignin: Impact on the Lignin Properties. Issue 1 (4th November 2013) - Saito, Tomonori; Perkins, Joshua H.; Vautard, Frederic; Meyer, Harry M.; Messman, Jamie M.; Tolnai, Balazs; Naskar, Amit K.
Abstract The development of technologies to tune lignin properties for high‐performance lignin‐based materials is crucial for the utilization of lignin in various applications. Here, the effect of methanol (MeOH) fractionation on the molecular weight, molecular weight distribution, glass transition temperature (Tg), thermal decomposition, and chemical structure of lignin were investigated. Repeated MeOH fractionation of softwood Kraft lignin successfully removed the low‐molecular‐weight fraction. The separated high‐molecular‐weight lignin showed a Tg of 211 °C and a char yield of 47 %, much higher than those of as‐received lignin (Tg 153 °C, char yield 41 %). The MeOH‐soluble fraction of lignin showed an increased low‐molecular‐weight fraction and a lower Tg (117 °C) and char yield (32 %). The amount of low‐molecular‐weight fraction showed a quantitative correlation with both 1/Tg and char yield in a linear regression. This study demonstrated the efficient purification or fractionation technology for lignin; it also established a theoretical and empirical correlation between the physical characteristics of fractionated lignins.